Row spacing and seed rating for irrigated wheat crop in the cerrado region in Brazil - Silva, Dijalma Barbosa da; Gomes, Antônio Carlos (Pesquisa Agropecuaria Brasileira, 2014)
Two field experiments were carried out during the 1985-1987 period wath sprinkler irrigation (Central Pivot), to verify the effects of plant density and row spacing in wheat (Triticum aestivum L.) production in Cerrado soils. The first experiment was set up in Planaltina, DF, Brazil, in 1985, with the wheat cultivar BR 12-Aruanã. The treatments combined three row spacings (0,17 x 0,17, 0,17 X 0,34 and 0,34 x 0,34 m) and three plant densities (200, 300 and 400 seeds/m2). In the second experiment the treatments included six plant densities (100, 150, 200, 250, 300 and 400 seeds/m2) and two wheat cultivars (Anahuac and BR 12-Aruanã). It was carried out in two places (Planaltina, DF and Rio Paranaíba, MG), for two years (1986 and 1987). The data from the first experiment indicate that the best row spacing treatment was 0,17 m which produced the higher grain yield/ha, heads/m2, tillers/plant, beads/plant and tillers surviving percent. There was no plant density effect on grain yield in the 1985 experiment, but in the second one the grain yield for both wheat varieties increased with plant density up to the level of 267 seeds/m2 , decreasing afterwards. Also, for both experiments as the plant density increased, there was a tendency to reduce the 1.000-grain weight, tillers/plant, heads/plant, grain number/heads and tillers surviving percent.